2004
DOI: 10.1159/000081305
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Allergic Effects of Lactic Acid Bacteria Are Strain Dependent and Mediated by Effects on both Th1/Th2 Cytokine Expression and Balance

Abstract: Background: There is growing interest in the immune-stimulating effect and in particular, the anti-allergic effect, of lactic acid bacteria (LAB). However, no comprehensive studies have been done that compare the immune-stimulating potential of LAB strains. Methods: The in vitro immune-stimulating effects on Th1/Th2 balance of more than 100 LAB strains were compared in splenocytes from ovalbumin-sensitized Th2-polarized mice. The in vivoanti-allergic ability of strain KW3110 was studied in the Th2-polarized mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
219
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(235 citation statements)
references
References 50 publications
12
219
1
3
Order By: Relevance
“…First, heat-killed cells of these strains were examined for in vitro production of IL-12, IFN-γ and IL-4 by splenocytes from OVA-immunized Balb/c mice, in order to select the strain with strong potential to modulate the Th1/ Th2 balance toward the Th1-dominant state. It has been reported that different Lactobacillus strains, even within the same species, show different patterns of IL-4 and IL-12 production (Fujiwara et al, 2004;Torii et al, 2007;Sakaguchi et al, 2008). In accordance with previous studies, our results strongest activity to suppress IL-4 production.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…First, heat-killed cells of these strains were examined for in vitro production of IL-12, IFN-γ and IL-4 by splenocytes from OVA-immunized Balb/c mice, in order to select the strain with strong potential to modulate the Th1/ Th2 balance toward the Th1-dominant state. It has been reported that different Lactobacillus strains, even within the same species, show different patterns of IL-4 and IL-12 production (Fujiwara et al, 2004;Torii et al, 2007;Sakaguchi et al, 2008). In accordance with previous studies, our results strongest activity to suppress IL-4 production.…”
Section: Discussionsupporting
confidence: 93%
“…Certain Lactobacillus strains can potentially modulate immune response through the production of interleukin-12 (IL-12), a potent stimulus for interferon-γ (IFN-γ) production, by antigen-presenting cells, such as dendritic cells (DCs) and macrophages, leading the population of type 1 helper T (Th1) cells and Th2 cells toward a Th1-biased state (Murosaki et al, 1998;Shida et al, 1998;Fujiwara et al, 2004). This effect might be of use in the prevention and treatment of allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[24][25][26] In this study, 117 strains isolated from fermented plant products were screened for strong inducers of IL-12 production in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…They were given a CRF-1 diet (Oriental Yeast, Tokyo, Japan) and water ad libitum for at least 1 week before the experiments. Experiments were performed according to the Guidelines for the Care and Use of Experimental Animals of the Japanese Association for Laboratory Animals.Reagents The reagents used in the experiments include OVA (Sigma, St. Louis, MO, USA), alum (LSL Co., Tokyo, Japan) and B. pertussis (Sigma).Measurement of ovalbumin-induced cytokines and ovalbumin-specific IgE The effects of oral administration of S. crispa on the antigen-induced production of cytokines and the antigen-specific IgE were investigated using a culture system with OVA-stimulated splenocytes derived from mice fed S. crispa as described by Fujiwara et al (2004) with some modifications. BALB/c mice (n = 8 per group) were intraperitoneally sensitized with 20 μg of OVA absorbed onto 2 mg of alum in 0.1 ml sterile saline.…”
mentioning
confidence: 99%